Fabrication of quasi-hexagonal Si nanostructures and its application for flexible crystalline ultrathin Si solar cells - Lee, Youngseok; Woo, Yeeun; Lee, Doh-Kwon; Kim, Inho (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Optimally designed Si nanostructures can serve as effective light trapping structures for flexible crystalline ultrathin Si solar cells. In this study, we develop a unique quasi-hexagonal inverted nano-pyramid in a hexagonal array, fabricated by a combined process of nanosphere lithography and wet etching. Self-assembled silica nanoparticles were deposited on Si wafers by spin coating, followed by deposition of triangular metal nanodisks in a hexagonal array. The metal nanodisks were used as a wet etch mask in an alkaline solution to create the quasi-hexagonal Si nanostructures. We investigated a temporal evolution of the Si nanostructures with increasing the etch time to optimize optical performances. The newly developed nanostructures take a quasi-hexagonal inverted pyramid, which provides geometrically high compatibility with the self-assembled monolayers in a hexagonal array. We incorporated these quasi-hexagonal nanostructures to the flexible crystalline ultrathin Si solar cells, and the novel nanostructures exhibited optical performances comparable to conventional micro-pyramid textures while showing the enhanced mechanical flexibility of the ultrathin Si-based solar cells.
Keywords: ELECTRON-BEAM LITHOGRAPHY; NANOSPHERE LITHOGRAPHY; NANOIMPRINT LITHOGRAPHY; SILICON; ARRAYS; NANOFABRICATION; SI(100)